Dengue-related cyberchondria in a Peruvian endemic area: exploratory analysis of demographic characteristics and mental health disorders in Human Medicine students - Rodriguez-Saldaña, Christian Alberto (2025)
Cyberchondria has intensified in contexts of infectious outbreaks, such as COVID-19, and may be influenced by local factors such as the endemicity of dengue in certain regions of Peru. Objective: To explore dengue-related cyberchondria among medical students in a dengue-endemic area in northern Peru. Materials and methods: A cross-sectional study was conducted at the National University of Piura, using self-reported questionnaires such as the Cyberchondria Severity Scale (CSS-12) and the Depression, Anxiety, and Stress Scale (DASS-21). Students without informed consent or with a recent diagnosis of dengue were excluded. Results: In a total sample of 192 participants, the average cyberchondria severity score was 27.7 ± 7.2. Significant variables included rural origin (p=0.029), being in the middle cycles of the course (p=0.001), and high levels of anxiety (p<0.001) and stress (p=0.030) according to the DASS-21. Multivariate analyses revealed that anxiety is a significant predictor of the severity of cyberchondria. Conclusion: Anxiety is a significant predictor of the severity of cyberchondria in medical students living in dengue-endemic areas.